PERANCANGAN SISTEM INFORMASI CATATAN SERVIS TEKNISI HAMA BERBASIS ANDROID PADA PT.RENTOKIL INITIAL INDONESIA CABANG TANGGERANG - Mahmud Safudin; Riswandi Ishak; Eko Yulianto3; Ricki Sastra4 (Jurnal Teknik Informatika, 2023)
In a industry, service record are very meaningful for industries engaged in service,because service records serve as atrack record of work and are proof of work by technicians to customer who have entered into service usage agreements wth the company. But at this time service records technicians perform service records manually which causes service records to be lost without a trace due to improper storage of service records. customer name, customer phone number and data that should not be disseminated. To facilitate service, maintain privacy and anticipate things that are not wanted in the service records, these technicians require computerized data collection using an Android-based information system that can store customer data that only the company and customers see, using an information-based system. Android can make it easier and useful for all parties, including the company between customers, companies and between these texts who perform updated service work to customers